Historical legacies and urbanization: Evidence from Chinese concessions - Gan Jin; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2024)
Can colonialism affect today's urban outcomes? This paper examines the long-run impact of Concessions - foreign-run enclaves established in the late nineteenth century inside Chinese cities by European settlers for residence and investment purposes. They soon became the new economic hubs of their hosting cities. By using a unique dataset of geo-referenced apartment transactions and by employing a spatial regression discontinuity approach to identify the causality, we find that apartments located inside historical Concession areas command a price premium of 17% compared to similar homes just outside of the Concession boundaries. We show that the long-run economic effect of Concessions may be explained by better access to urban facilities in these areas.
Keywords: N95; O18; O43; P48; R5; 330; Colonialism; Housing price; Urbanization; Persistence; China